The Influence of Social Identity, Self-Concept and Learning Motivation on the Motor Ability of Elementary School Students - Ahadin; Safiah, Intan; Yunus, Muhammad; Razali; Masri (Journal of Education and e-Learning Research, 2024)
This study aims to examine the factors that influence the motor abilities of elementary school students. The following aspects were explored: 1) The influence of social identity on students' motor abilities. 2) The influence of self-concept on students' motor abilities. 3) The influence of learning motivation on students' motor abilities. 4) The simultaneous influence of social identity, self-concept and learning motivation on students' motor abilities. In this study, a quantitative method was employed to investigate the relationship between the three aforementioned factors and motor ability among 128 elementary school students in Banda Aceh City. The data collection process involved the use of structured questionnaires which were employed to gather relevant information. Multiple regressions were used to analyse the data with the use of SPSS version 23 software. The obtained results from this study showed that both social identity and learning motivation positively and significantly influenced the motor ability of the observed students while self-concept had no discernable impact. However, when simultaneously considering these variables altogether, it was found that they did significantly influence the skills of the students. In a nutshell, the results of this study indicated that there was a positive relationship between social identity and the motor ability of the students. The implications of this research show that to improve students' motor abilities, efforts must also be made to increase social identity and learning motivation.